The effect of sourcing strategies on the relationship between competitive strategy and firm performance - Abdullah, Haim Hilman; Mohamed, Zainal Abidin; Othman, Rozhan; Uli, Jegak (World Business Institute, 2009)
The paper presents a study which seeks to add to the body of knowledge that relates Porter’s generic strategies, and sourcing strategies to organizational performance in the context of Malaysia manufacturing industry. Using mail survey, the study first identified the natural taxonomy of two strategic types of manufacturing firms, based on their use of Porter’s generic strategies in pure form, and sourcing strategies of make and buy options. The study examined specific strategic types were associated with specific sourcing strategies. The findings indicate the cost leadership strategy that is mediated by make strategy generate better performance than other types of association. Similar to the relationship between differentiation strategy and organizational performance which mediated by buy strategy, have superior performance than other type of association. The study concludes that the research provided body of knowledge relevant for the Malaysia manufacturing industry, which may be used by top management in the industry in the strategy formulation process as well as by the researches in exploring the influence of different contingencies on manufacturing industry’s strategic orientation.